ANALISIS PENGOLAHAN LIMBAH PADAT DAN CAIR INDUSTRI KERIPIK SINGKONG TERHADAP LINGKUNGAN MASYARAKAT - Anisa Fitri Handaris Purba; Sefira Aulia Harahap; Widyana; Abdurrozzaq Hasibuan (CV. ADIBA AISHA AMIRA, 2023)
Introduction: Waste is the result of residue or waste from a production activity, such as the cassava chips industry which produces solid and liquid waste in its production activities. Both types of waste will have a negative impact if the waste is not treated. The waste from processed cassava which often has a negative impact is liquid waste. The aim of this research is to analyze the processing of solid waste and liquid waste generated from the cassava chips industry and their impact on the environment. Method: This research is a qualitative research. Data obtained from direct observation and interviews. The research subjects are the cassava chip industry owners and the longest-serving workers in the industry. The research instruments consisted of researchers, interview question texts, stationery, and voice recorders. Presentation of data descriptively based on the results as they are. Result: Some of the waste generated is processed and some is not processed. Solid waste that is not processed is waste cassava peels and cassava cobs. The sediment waste from cassava soaking water is processed into mocaf flour. Meanwhile, the liquid waste produced is not processed. Conclusion: The cassava chips industry studied only produces mocaf flour as a new product from the utilization of the waste produced. The impact of cassava chips liquid waste is to contaminate water and soil, and stagnant wastewater becomes a breeding ground for disease vectors